Pengujian Campuran SMA Kasar Menggunakan Batu Sungai Tapparan Kabupaten Tana Toraja - Emil Loli; Alpius; Charles Kamba (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
This experiment is to intended of Tapparan river stone in a Stone Matrix Asphalt (SMA). The method in this experiment is to test character of every agregate and filler. then make a composition of Stone Matrix Asphalt (SMA) mixture Marshall testing to get the characteristics and the Marshall Immersion test for the remaining Marshall Stability value. The results of research, shows the character of the pavement material in the form of Tapparan River rock, Tana Toraja Regency, meet some specific for coating material. with conventional Marshall Test, the characteristics with asphalt content of 6.00%, 6.25%, 6.50%, 6.75%, and 7.00% meet the General Specifications. From the Marshall Immersion test, it was obtained that the remaining Marshall Stability was 95.10% with asphalt 7.00% fulfilling the requirements, namely> 90% accordance with the General Specifications.